A Note on Scalar-Valued Gap Functions for Generalized Vector Variational Inequalities - Xiang-Kai Sun; Hong-Yong Fu; Yi Chai (Abstract and Applied Analysis)
This paper is concerned with gap functions of generalized vector variational inequalities (GVVI). By using scalarization approach, scalar-valued variational inequalities of (GVVI) are introduced. Some relationships between the solutions of (GVVI) and its scalarized versions are established. Then, by using these relationships and some mild conditions, scalar-valued gap functions for (GVVI) are established.